Development of methods and feasibility of using hyperpolarized carbon‐13 imaging data for evaluating brain metabolism in patient studies. Issue 3 (10th January 2018) - Park, Ilwoo; Larson, Peder E.Z.; Gordon, Jeremy W.; Carvajal, Lucas; Chen, Hsin‐Yu; Bok, Robert; Van Criekinge, Mark; Ferrone, Marcus; Slater, James B.; Xu, Duan; Kurhanewicz, John; Vigneron, Daniel B.; et al.
Abstract : Purpose: Hyperpolarized carbon‐13 ( 13 C) metabolic imaging is a noninvasive imaging modality for evaluating real‐time metabolism. The purpose of this study was to develop and implement experimental strategies for using [1‐ 13 C]pyruvate to probe in vivo metabolism for patients with brain tumors and other neurological diseases. Methods: The 13 C radiofrequency coils and pulse sequences were tested in a phantom and were performed using a 3 Tesla whole‐body scanner. Samples of [1‐ 13 C]pyruvate were polarized using a SPINlab system. Dynamic 13 C data were acquired from 8 patients previously diagnosed with brain tumors, who had received treatment and were being followed with serial magnetic resonance scans. Results: The phantom studies produced good‐quality spectra with a reduction in signal intensity in the center attributed to the reception profiles of the 13 C receive coils. Dynamic data obtained from a 3‐cm slice through a patient's brain following injection with [1‐ 13 C]pyruvate showed the anticipated arrival of the agent, its conversion to lactate and bicarbonate, and subsequent reduction in signal intensity. A similar temporal pattern was observed in 2D dynamic patient studies, with signals corresponding to pyruvate, lactate, and bicarbonate being in normal appearing brain, but only pyruvate and lactate being detected in regions corresponding to the anatomical lesion. Physiological monitoring and follow‐up confirmed that there were no adverse events associated with the injection. Conclusion: This study has presented the first application of hyperpolarized 13 C metabolic imaging in patients with brain tumor and demonstrated the safety and feasibility of using hyperpolarized [1‐ 13 C]pyruvate to evaluate in vivo brain metabolism. Magn Reson Med 80:864–873, 2018. © 2018 International Society for Magnetic Resonance in Medicine.